EFEKTIVITAS DANA BOS TERHADAP PENINGKATAN MUTU DI MADRASAH - Sumarni Sumarni (Badan Litbang dan Diklat Kementerian Agama RI, 2014)
This study attempts to know the fund management of Bantuan Operasional Sekolah (BOS/School Operational Assistance) in Madrasah Ibtidaiyah (MI) and Madrasah Tsanawiyah (MTs) and also its effectiveness in improving the education quality in madrasah. The research was conducted in 12 provinces with 144 MI and 98 MTs samples in total. The data were collected using instrument of questionnaires, interview guides, checklists, and being analyzed using SPSS Version 19. The research result shows that, first, the performance of BOS fund management has been very positive. The positive side of this BOS fund management is seen from the level of preparation, the implementation process, and activities after the implementation, its derivative impacts, and general evaluation toward the performance of BOS Team of the madrasah. Second, the BOS fund have avery positive impact towards the quality improvement of madrasah which is measured with the indicators of improved accreditation status of madrasah, increasing number of students, and the (decreasing) number of not-grade and drop-out students. The positive impact of BOS is also recorded from the achievement of madrasah students in many and various contests. In addition to that, the BOS fund is able to increase the ethos of school and learning spirit of the students.